1989
DOI: 10.1590/s0036-46651989000600003
|View full text |Cite
|
Sign up to set email alerts
|

Potential infectivity of blood from HBsAG asymptomatic carriers due to the presence of HBV-DNA and comparison with other markers of hbv infection

Abstract: SUMMARY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…These results are in agreement with the studies accomplished by TEDESCHI et al (1989) 38 and CHIARAMONTE et al (1991) 11 although they differ from other studies in which it has been observed higher indexes of detection for HBV-DNA by PCR 2,16,27 and Dot-blot 26 .…”
Section: Discussionsupporting
confidence: 90%
“…These results are in agreement with the studies accomplished by TEDESCHI et al (1989) 38 and CHIARAMONTE et al (1991) 11 although they differ from other studies in which it has been observed higher indexes of detection for HBV-DNA by PCR 2,16,27 and Dot-blot 26 .…”
Section: Discussionsupporting
confidence: 90%